The role of the nurse in the neonatal intensive care unit: between the ideal, the real and the possible Actuación de la enfermera en la unidad de terapia intensiva neonatal: entre lo ideal, lo real y lo posible Atuação da enfermeira na unidade de terapia intensiva neonatal: entre o ideal, o real e o possível - Liciane Langona Montanholi; Miriam Aparecida Barbosa Merighi; Maria Cristina Pinto de Jesus (Universidade de São Paulo, 2011)
The nurse is one of the professionals responsible for the care directed toward the physical, mental and social development of newborns in the Neonatal Intensive Care Unit. This study aimed to comprehend the experience of nurses working in a Neonatal Intensive Care Unit. Data collection was performed in 2008, through interviews with 12 nurses working in public and private hospitals of the city of São Paulo. The units of meaning identified were grouped into three categories: Developing actions; Perceiving their actions and Expectations. The analysis was based on social phenomenology. It was concluded that the overload of activities, the reduced number of staff, the lack of materials, equipment and the need for professional improvement are the reality of the work of the nurse in this sector. To supervise the care is the possible; integral care of the newborn, involving the parents, is the ideal desired. El enfermero es uno de los profesionales responsables por el cuidado dirigido al desarrollo físico, psíquico y social del recién nacido en la Unidad de Terapia Intensiva Neonatal. Este trabajo objetivó comprender la experiencia de enfermeras que actúan en una Unidad de Terapia Intensiva Neonatal. La recolección de datos fue realizada en 2.008, por medio de entrevistas con 12 enfermeras que actuaban en hospitales públicos y privados de la ciudad de Sao Paulo. Las unidades de significado identificadas fueron agrupadas en tres categorías: Desarrollando acciones, Percibiendo sus acciones y Expectativas. El análisis fue fundamentado en la fenomenología social. Se concluye que la sobrecarga de actividades, el reducido número de personal, la falta de materiales, equipamientos y la necesidad de perfeccionamiento profesional son la realidad del trabajo de la enfermera en ese sector. Supervisar los cuidados, es posible; cuidar integralmente del recién nacido, envolviendo sus padres, es el ideal deseado. O enfermeiro é um dos profissionais responsáveis pelo cuidado voltado ao desenvolvimento físico, psíquico e social do recém-nascido na unidade de terapia intensiva neonatal. Este trabalho objetivou compreender a experiência de enfermeiras que atuam em uma unidade de terapia intensiva neonatal. A coleta de dados foi realizada em 2008, por meio de entrevistas com 12 enfermeiras que atuavam em hospitais públicos e privados da cidade de São Paulo. As unidades de significado identificadas foram agrupadas em três categorias: desenvolvendo ações, percebendo suas ações e expectativas. A análise foi fundamentada na fenomenologia social. Conclui-se que a sobrecarga de atividades, o reduzido número de pessoal, a falta de materiais, equipamentos e a necessidade de aprimoramento profissional são a realidade do trabalho da enfermeira nesse setor. Supervisionar os cuidados é o possível; cuidar integralmente do recém-nascido, envolvendo seus pais, é o ideal almejado.